3D Carbon Networks Constructed NaVPO4F/C/rGO as a Cathode Material for High-Performance Sodium-Ion Batteries - Guo, Jin-Zhi; Yang, Ai-Bo; Zhao, Xin-Xin; Gu, Zhen-Yi; Wu, Xing-Long (Frontiers in Energy Research, 2020)
The fluorophosphate NaVPO4F (NVPF) is a good candidate of cathode material for sodium-ion batteries (SIBs) due to its high theoretical specific capacity, high working voltage and stable structure. However, due to the low electronic conductivity of NVPF, its electrochemical properties are difficult to demonstrate. In order to address the insufficient and then enhance its electrochemical performance, a 3D carbon networks constructed NaVPO4F/C/rGO (NVPF/C/rGO) nanocomposite is prepared by freeze-drying assisted high-temperature solid-state method. When used as a cathode material for SIBs, the prepared NVPF/C/rGO can deliver a capacity of about 108.7 mA h g-1 at 0.05 C. Moreover, NVPF/C/rGO nanocomposite also exhibits the excellent electrochemical performance, including superior rate capacities (about 65.8 mA h g-1 specific capacity at 10 C) and outstanding cycling performance ( 95.1 % capacity retention after 200 cycles at 0.05 C), which can be attribute to the 3D carbon networks and the nanoparticles in NVPF/C/rGO nanocomposite. The preliminary results illustrate that the 3D carbon networks constructed NVPF/C/rGO could be a promising cathode material for SIBs.